2007
DOI: 10.1002/hed.20559
|View full text |Cite
|
Sign up to set email alerts
|

Galectins as modulators of tumor progression in head and neck squamous cell carcinomas

Abstract: Head and neck squamous cell carcinomas (HNSCCs) remain a significant cause of morbidity worldwide. Biological therapies able to induce and/or upregulate antitumor immune responses could represent a complementary approach to conventional treatments for patients with HNSCC because, despite advances in surgery, radiotherapy, and chemotherapy, the overall survival rates for these patients have not changed over recent decades. Galectins are involved in the control of cell proliferation, cell death, and cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 93 publications
6
41
0
4
Order By: Relevance
“…The role of Gal-1 in angiogenesis seems to be tissue-specific as Gal-1 expression correlates with endothelial cell markers in advanced prostate cancer but not in human breast cancer. These findings are consistent with the ability of Gal-1 to induce angiogenesis in oligodendroglioma (30), B16 melanoma (31), and Kaposi's sarcoma (26) but not in other tumor types such as Lewis lung carcinoma (41).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The role of Gal-1 in angiogenesis seems to be tissue-specific as Gal-1 expression correlates with endothelial cell markers in advanced prostate cancer but not in human breast cancer. These findings are consistent with the ability of Gal-1 to induce angiogenesis in oligodendroglioma (30), B16 melanoma (31), and Kaposi's sarcoma (26) but not in other tumor types such as Lewis lung carcinoma (41).…”
Section: Discussionsupporting
confidence: 83%
“…Given the pleiotropic functions of Gal-1 in the tumor microenvironment, including its role in angiogenesis (26,31,39,40), cell adhesion and invasiveness (16,30), and immunosuppression (23)(24)(25)41), upregulation of Gal-1 may dramatically influence prostate cancer progression. In this regard, Gal-1 is expressed in endothelial cells (42)(43)(44) and is upregulated in various cancer types (6).…”
Section: Discussionmentioning
confidence: 99%
“…Each monomer is composed of a carbohydrate-recognition domain that recognizes a wide range of glycoproteins and glycolipids (13). Gal-1 expression in cancer-associated stroma is correlated with poor survival in several types of cancer including breast, prostate, and head and neck cancers (14)(15)(16)(17). We previously reported (18) that increased Gal-1 expression in cancer-associated stroma and the tumor-invasive front is significantly correlated with a poor prognosis in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Our study identified the involvement of galectin-3 (Gal-3), a member of the β-gal-binding galectin family of proteins, in BMME-mediated cell proliferation, protection, and BM lodgment. Gal-3 associates with cell proliferation, migration, adhesion, and apoptosis (22)(23)(24)(25)(26), and moreover is associated with disease progression, metastasis, and drug resistance in various cancers (27)(28)(29)(30)(31), but the role of Gal-3 in leukemia has remained largely unknown.…”
mentioning
confidence: 99%